The Significance of Entrepreneurial Leadership in Armed Forces Hospitals - Dian Andriani Ratna Dewi; Lila Irawati Tjahjo Widuri; Ni Made Wiliantari; Sherryn Sherryn (The ASEAN Journal of Military and Preventive Medicine, 2024)
Background: Currently, merely possessing leadership or entrepreneurial qualities is insufficient for assuming the role of a hospital head in the armed forces. Successful hospital leadership necessitates the embodiment of Entrepreneurial Leadership (EL), a contemporary model combining leadership excellence with an entrepreneurial spirit. The capacity of a hospital to advance is profoundly shaped by its economic acumen, and to thrive, leaders surpassing EL standards are imperative. Methods: A scoping review was conducted utilizing the Google Scholar database and PubMed, adhering to the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) statement guidelines. A total of 136 articles from various studies conducted between 2018 and 2023, spanning diverse countries, were reviewed. Extraction focused on 5 studies from 4 countries that implemented leadership interventions among doctors, dentists, and hospitals. Discussion: In light of the global impact of the COVID-19 pandemic, the landscape of hospital management is undergoing rapid transformation. Internet-based technologies are becoming essential for hospitals to address service requirements and enhance efficiency, thereby increasing overall effectiveness. Only leaders possessing EL can ensure the survival, development, and competitiveness of hospitals amidst these evolving challenges. Conclusion: The characteristics of EL exhibited by hospital leaders significantly influence the performance, continuity, effectiveness, and productivity of competitive hospital enterprises. The application of EL enables hospitals to attain superiority, professionalism, resilience, innovation, and adaptability to various changing conditions.